THE IMPACT OF IRANIAN FILMS AND TELEVISION SERIES ON TURKISH AND AZERBAIJANI INBOUND TOURISTS - Salehi, Hassan; Lam, Adam (International Journal of Research -GRANTHAALAYAH, 2024)
Recently, Iran has employed different methods to attract international tourists, with film tourism emerging as one of the most effective strategies, owing to the export of television (TV) series and films. With this tool and approach, Iran increased the number of tourists and became a unique country to visit owing to the shared language, culture, and special geographic location with over 15 countries, including two independent and disconnected states in Iraq, Azerbaijan, Kurdistan, and Nakhichevan, alongside 27 heritage sites. Iran achieved remarkable success in exporting TV series and films. The ‘film-induced tourism effect’, which refers to the increase in demand for travel to Iran, is widely thought to be one of the most significant outcomes of exporting TV series and films. This relatively new field explores how TV series and films affect travel demand. The main purpose of this study is to analyse the impact of TV series broadcasting in other countries with cultural similarities such as language. For this, we examine the influence of Turkish and Azerbaijani citizens visiting Iran. The results indicate that visitors from both countries were affected by Iranian TV series post-2018.